THE INFLUENCE OF WORK LIFE BALANCE AND WORK ENVIRONMENT ON THE PERFORMANCE OF GENERATION Z EMPLOYEES (STUDY ON STUDENTS OF THE MANAGEMENT STUDY PROGRAM AT MUHAMMADIYAH TANGERANG UNIVERSITY, CLASS OF 2021) - Nurizky, Muhamad Irfan; Soemadi, Anggraini (Penelitian dan Pengembangan Ilmu, 2025)
This study aims to determine and explain the effect of Work Life Balance and Work Environment on Generation Z Employee Performance (Study on Management Study Program Students, University of Muhammadiyah Tangerang Class of 2021). This research uses a quantitative approach with a type of survey method. The sample determination in this study used a saturated sample technique, which is a sampling technique when all members of the population are used as samples. The sample in this study were 111 respondents. The data obtained were analyzed using PLS (Partial Least Square) technique through Smartpls 4.0 software. The results of this study indicate that work life balance variables have a significant effect on employee performance, work environment variables have a significant effect on employee performance. The results of the analysis in this study indicate that the work life balance and work environment variables simultaneously have a significant effect on employee performance.